Characteristics and analysis of dynamic strain response on typical asphalt pavement using Fiber Bragg Grating sensing technology. (6th December 2021) - Liu, Hongfu; Ge, Wenwen; Pan, Qinxue; Hu, Rong; Lv, Songtao; Huang, Tuo
Highlights: The surface courses' dynamic longitudinal strain response peaks at different lateral positions showed the double hump law. The base courses' dynamic longitudinal strain response peaks at different lateral positions showed the single hump law. The dynamic longitudinal strain response change law of four different base types of asphalt pavement was revealed. Abstract: The purpose of this research was to reveal the dynamic strain response characteristics and variation law of asphalt pavement structure with different base types under traffic load, and provide reliable measured data for the development of a pavement structure design method combined with China's national conditions and highway construction characteristics. Four types of base pavement were designed, cement treatment base, cement treatment base + graded gravel base, asphalt treatment base + cement treatment base, and asphalt treatment base + graded gravel base asphalt pavement. The dynamic responses of four kinds of asphalt pavements at different transverse positions, depths, and speeds under 100 kN loading conditions were tested using fiber Bragg grating sensors. The results show that the longitudinal strain at the bottom of the surface courses under dynamic load reveals the compressive-tensile-compressive alternating law. The longitudinal strain at the bottom of the base courses is mainly tensile strain. The maximum peak value of the surface courses appears at the corresponding single wheel load center. The maximum peak value of the base courses appears at the corresponding dual-wheel gap center. The faster the traveling speed is, the shorter the loading time of each structural layer of asphalt pavement, and the higher the loading frequency is. The loading position has a significant influence on the peak value of dynamic strain response. Reducing the cement-treated base course's strength and stiffness appropriately and ensuring the continuity of each layer's modulus to the greatest extent will benefit each structural layer's dynamic strain response distribution and improve the bearing capacity and durability of each layer of asphalt pavement against a heavy load.